How Tourism Crisis Influenced Tourist Consumption Behaviour towards the Affected Destination --- A case study of SARS in Hong Kong - DU, MINJUN (2006)
The tourism industry as one of the most vulnerable and fragile industries to crises has suffered the dramatic impact of recent major events from epidemics to terrorist attacks. These so called tourism crises are regarded as the perception of danger and uncertainty by tourists, which causes negative consumption behaviour towards the affected destinations. This dissertation explores the impact of tourism crises on tourist consumption behaviour towards affected destinations and their tourism industries. The SARS epidemic in Hong Kong in 2003 is selected as a case with which to examine the immediate impact of tourist consumption behaviour on Hong Kong during the event and for investigation of the post-event impact on potential tourists buying behaviour towards Hong Kong. A questionnaire survey was conducted with a sample of 103 potential tourists. The data was analysed using multivariate analysis techniques. The results indicated that SARS caused negative consumption behaviour in the form of altering tourists travel decisions towards Hong Kong and resulted in low travel intentions during its outbreak period, while the post-SARS impact presented several changes in the decision-making process of holiday consumption towards Hong Kong, such as in hygiene and safety concerns in decision-making. Several factors, like risk perception, were found to predict the variance of tourist consumption behaviour towards Hong Kong due to SARS. Several demographic factors were also discovered to be significant predictors.